Transcatheter Mitral Valve Repair in a Patient with Osteogenesis Imperfecta: A Case Report and Literature Review - Merna Hassan; Yosef Manla; Nadya Almatrooshi; Yazan Aljabery; Guirgis Gabra; Feras Bader; Mahmoud Traina; Emad Hakemi (Interventional Cardiology: Reviews, Research, Resources)
With the emergence of less invasive transcatheter valvular therapies, there remains a limited understanding of the feasibility and durability of these approaches in patients with osteogenesis imperfecta and whether they can offer a suitable alternative to conventional surgery. In this context, and with a focus on mitral repair, we report on a case of mitral transcatheter edge-to-edge repair in a patient with osteogenesis imperfecta and conduct a comprehensive review of the characteristics and outcomes of reported osteogenesis imperfecta cases undergoing surgical or transcatheter mitral repair. Given the high burden of complications of surgery in this population, transcatheter mitral repair could potentially serve as a suitable alternative to conventional surgery in this challenging population.